Agressive central giant cell granuloma of the mandible: case report - Durão, Ana Reis; Koch, José Teixeira; Miranda, Marcelo; Aline, Aline Morosolli (Brazilian Dental Science, 2015)
Central giant cell granulomas (CGCG) are benign intraosseous proliferative lesions. Usually located are at the anterior region of the maxilla or mandible, although are more frequently found in the mandible. Etiopathogenesis of these lesions has remained unknown, however, some consider them as reparative response rather than neoplastic condition. Clinically CGCG present as asymptomatic, with expansive swelling causing deviation or proliferation of cortical bone. This condition is usually unifocal. Surgical removal is often the preferred treatment. Although nonsurgical treatment methods, such as intralesional corticosteroid injections, systemic calcitonin and interferon have been reported. This article describes the radiographic features of a large CGCG in the anterior mandibular region seen in a 9 year-old patient. Treatment of this lesion included resection of the anterior region of the mandible and replacement by tibia with bone growth factors. Keywords: Central giant cell granuloma; reparative granulomas; mandible; jaws.